Cross-sectional adherence with the multi-target stool DNA test for colorectal cancer screening: Real-world data from a large cohort of older adults. (March 2021) - Weiser, Emily; Parks, Philip D; Swartz, Rebecca K; Thomme, Jack Van; Lavin, Philip T; Limburg, Paul; Berger, Barry M
Objective: To determine cross-sectional adherence with the multi-target stool DNA test used for colorectal cancer screening in a large, fully insured Medicare population. Methods: All patients aged 65–85 with a valid multi-target stool DNA test order from 1 September 2016 to 31 August 2017 identified from the Exact Sciences Laboratories (Madison, WI; sole-source national multi-target stool DNA test provider) database were evaluated for test adherence. Cross-sectional adherence, defined as multi-target stool DNA test completion within 365 days from order date, was analyzed overall and by time to adherence, as well as by available patient (age, sex, test order date, Medicare coverage type) and provider (specialty, year of first multi-target stool DNA test order, multi-target stool DNA test order frequency, and practice location) factors. Results: Among 368, 494 Medicare beneficiaries (64% female), overall cross-sectional adherence was 71%. Cumulative adherence rates increased more rapidly at 30 (44%) and 60 (65%) days, followed by more gradual increases at 90 (67%), 180 (70%), and 365 (71%) days. By provider specialty, primary care clinicians represented a higher percentage of multi-target stool DNA orders than gastroenterologists (88% vs. 6%), but had a lower associated patient adherence rate (71% vs. 78%). Conclusions: In this large, national sample of Medicare insured older adults, nearly three-quarters of patients adhered with a multi-target stool DNA order for colorectal cancer screening. These real-world data should inform further clinical and population health applications, reimbursement model simulations, and guideline-endorsed colorectal cancer screening strategies adherence.